2020
DOI: 10.1038/s41598-020-73524-z
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of visual proportion of Gleason 4 and maximum cancer core length quantified by histopathologists

Abstract: Gleason score 7 prostate cancer with a higher proportion of pattern 4 (G4) has been linked to genomic heterogeneity and poorer patient outcome. The current assessment of G4 proportion uses estimation by a pathologist, with a higher proportion of G4 more likely to trigger additional imaging and treatment over active surveillance. This estimation method has been shown to have inter-observer variability. Fifteen patients with Prostate Grade Group (GG) 2 (Gleason 3 + 4) and fifteen patients with GG3 (Gleason 4 + 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cores were measured immediately after each biopsy (to minimise desiccation) by an independent operator (J.B.), in consensus with an operator not performing the biopsy procedure, to minimise bias. Each core was straightened (if necessary) on a piece of white card, and core length (CL)–the total length of the biopsy core (target + background material) and target length (TL)–(target material length only) marked alongside the core using an ultrafine (0.1 mm) black tip pen (adapted from [ 13 ]), and measured using a ruler to the nearest 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Cores were measured immediately after each biopsy (to minimise desiccation) by an independent operator (J.B.), in consensus with an operator not performing the biopsy procedure, to minimise bias. Each core was straightened (if necessary) on a piece of white card, and core length (CL)–the total length of the biopsy core (target + background material) and target length (TL)–(target material length only) marked alongside the core using an ultrafine (0.1 mm) black tip pen (adapted from [ 13 ]), and measured using a ruler to the nearest 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…grade groups 1 vs. 2) and that artificial intelligence performs remarkably well in this regard, highlighting the advantage of artificial intelligence to make consistent decisions. In addition to the Gleason score, it is recommended to report the portion of tumorous biopsy, the portion of Gleason pattern 4, a somewhat tedious task, which has been shown to be concerningly variable [9] and in one study was found over-estimated compared with digital analysis (mean bias of +14%) [10].…”
Section: Grade and Let Gradementioning
confidence: 99%
“…2 Indeed, previous series have reported the association of increasing %GP4 with adverse pathology and BCR. 8–10…”
mentioning
confidence: 99%